PkM Sarapan Sehat untuk Meningkatkan Konsentrasi Belajar - Ariyanto, Ariyanto; Fatmawati, Tina Yuli; Efni, Nel (3031-8572, 2023)
Society in Indonesian still don't get used to breakfast. In fact, not breakfast will have a negative impact on the learning process at school for school children, reducing physical activity, causing obesity in teenagers and adults, and increasing the risk of unhealthy snacks. Breakfast is food consumed in the morning whose function is to supply blood sugar levels. Children who skip breakfast will affect brain performance, where breakfast has the benefit of providing energy to the brain so that it can help improve memory, reduce the risk of anemia and concentrate when studying. The aim of this community service is for students to understand the health benefits of breakfast so that they can increase study concentration and improve health. This community service method includes lectures and discussions. Service activities were carried out for 25 students at SMP N 19 Jambi City. The results of this community service obtained an average student knowledge before education of 5.6 and after education of 8.9. This means that there was an increase in students' knowledge before and after education with an average increase of 3,3